1996
DOI: 10.1055/s-2007-972893
|View full text |Cite
|
Sign up to set email alerts
|

Pulse Wave Velocity Measurement by Cross-Correlation of Doppler Velocity Signals. Application to Elderly Volunteers During Training

Abstract: Pulse wave velocity (PWV) measurement is widely used for the indirect assessment of arterial wall distensibility. In order to improve its measurement technique, we built a system performing the calculation of the cross-correlation function of Doppler velocity signals. In 12 normal subjects and 10 patients, the mean difference between duplicate measurements was 0.7 +/- 7.8% (NS). We tested this technique in 15 elderly volunteers before and after a three months training period. Brachial and tibial systolic blood… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

1999
1999
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 3 publications
0
7
0
Order By: Relevance
“…But PWV has both structural and functional components, the former including both the collagen/elastin ratio and the thickness of the artery wall while the latter is largely dependant on factors such as MAP. Therefore, as mentioned in several reports [7,8,16], the effect of MAP on the elastic modulus of the arterial wall should be evaluated before any attempt is made to interpret differences in PWV. In the present study, different MAPs cannot be wholly responsible for the observed difference in PWVUL between trained and untrained children, since PWVUL was still lower in untrained boys, when MAP was fixed as a covariate.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…But PWV has both structural and functional components, the former including both the collagen/elastin ratio and the thickness of the artery wall while the latter is largely dependant on factors such as MAP. Therefore, as mentioned in several reports [7,8,16], the effect of MAP on the elastic modulus of the arterial wall should be evaluated before any attempt is made to interpret differences in PWV. In the present study, different MAPs cannot be wholly responsible for the observed difference in PWVUL between trained and untrained children, since PWVUL was still lower in untrained boys, when MAP was fixed as a covariate.…”
Section: Discussionmentioning
confidence: 99%
“…Briefly, PWV of the left upper limb was evaluated by a dedicated continuous wave Doppler and photoplethysmography system (AtysWave, Atys Medical, Soucieuen-Jarrest, France) as described previously [8]. The photoplethysmography probe was placed on the tip of the middle finger, and the continuous wave Doppler probe recorded the signal from the subclavian artery at the clavicle level.…”
Section: Pulse Wave Velocity Measurementmentioning
confidence: 99%
“…On the other hand, the palpating pressure waveform in peripheral arteries of superficial sites can be measured with high-fidelity tonometry pressure transducers (Kelly et al 1989a). Because the pressure pulse and flow propagate at the same velocity, the regional arterial PWV can be measured noninvasively by using the transit time of Doppler velocity signals or pressure waveforms detected at two sites with given separation (Dauzat et al 1996;Kingwell et al 1997;Lehmann et al 1993b).…”
Section: Introduction and Literaturementioning
confidence: 99%
“…Intimal-medial thickness (IMT) and pulse wave conduction velocity (PWCV) are structural and functional parameters, respectively, that can be reproducibly and noninvasively determined in large arteries (2,3). Abnormalities in these parameters may precede the formation of atherosclerotic plaque or may be markers for generalized atherosclerosis.…”
mentioning
confidence: 99%